Prediction and Prophylaxis of Preeclampsia: An Expert Review - Ozdemir, Ozge; Madazli, Riza; Mendilcioglu, Inanc; Ergun, Ali (Gynecology Obstetrics & Reproductive Medicine, 2025)
Preeclampsia remains one of the leading causes of global maternal and perinatal morbidity and mortality. This review aims to provide a comprehensive, up-to-date synthesis of the current evidence on prediction and prophylaxis strategies for preeclampsia. It particularly emphasizes the role of mean arterial pressure and combined screening models. A comprehensive literature review was conducted using PubMed and other relevant databases, focusing on studies published over the last two decades. Predictive approaches were evaluated, including maternal risk factors, biochemical markers, uterine artery Doppler scan, and mean arterial pressure. The review also discusses prophylactic interventions such as low-dose aspirin and calcium supplementation. Results from recent multicenter trials highlight the value of integrating maternal history with mean arterial pressure and biochemical markers. This approach improves screening performance in early pregnancy. This review underscores the importance of early risk stratification and timely initiation of preventive strategies to reduce the burden of preeclampsia. Its original value lies in presenting a concise, evidence-based update for clinical practice by integrating current guidelines with recent trial outcomes.